Geophysical Investigation on the Fracture distribution of Iwo-Olupona area, South-Western Nigeria using VLF em techniques. - SULEMAN Kamaldeen Olasunkanmi (University of El Oued, 2017)
This work uses Very Low Frequency Electromagnetic (VLF-EM) method to investigate the subsurface structure on a proposed Housing estate in Iwo, South-Western Nigeria with coordinates 7° 36’ 36.3” N and Longitude≈ 4° 12’ 06.6” E. The average VLF frequency employed during the field work is 20.8 kHz with average signal strength of 17dBm and the measuring interval of 20m. The data obtained by the VLF-EM method were analysed by 2D line Plotting. Raw real, R (In phase) and the imagining, I (quadrature) components were measured on the field. The Raw Real and filtered real data were plotted against stations on the same graph using excel, the graphs obtained are sinusoidal in shape with the peak indicating a conductive zones, resulting from weak geologic materials that may be due to fracture, joints, crack, and the trough indicates a non-conductive zones, associated with competent material which may be attributed to fresh basement material or resistive geological formation.
Keywords: Fracture; conductive zone; weak zone; structural displacement; frequency